Game-Based Learning through Board Games in Immunology: An Analysis of Conceptual Mastery and Cognitive Anxiety - Regina Anindya Putri; Adi Rahmat; Dewi Susanti; Sariwulan Diana; Muhamad Wafda Jamil (Jurnal Pendidikan Sains Indonesia, 2026)
Game-based learning has been widely developed as an instructional approach to enhance student engagement. One of its implementations takes the form of board games, which offer interactive and hands-on learning experiences. However, studies specifically examining their application to complex biology topics, such as the immune system, remain limited. Furthermore, few studies have simultaneously examined the effects on conceptual understanding and cognitive anxiety. Therefore, this study aims to analyze the impact of using board games on students’ mastery of immune system concepts and cognitive anxiety. This study employed a quasi-experimental design involving an experimental group (n = 30) and a control group (n = 32). Research instruments included a conceptual mastery test and the cognitive test anxiety scale (CTAS) questionnaire to measure students’ cognitive anxiety. The data were analyzed using inferential statistical tests and correlation tests to examine the relationships among the variables. The results of the study show that there were no significant differences in conceptual understanding or cognitive anxiety between the two groups, nor was a significant relationship found between the two. These findings suggest that the use of board games with complex subject matter does not always have a significant impact on cognitive or affective outcomes, although they hold the potential to promote a more positive learning experience